2017
DOI: 10.1111/jvp.12389
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of valnemulin after intravenous, intramuscular, and oral administration in layer chickens

Abstract: The pharmacokinetic characteristics of valnemulin in layer chickens were studied after single intravenous, intramuscular, and oral administration at a dose of 15 mg/kg body weight. Plasma samples at certain time points were collected and the drug concentrations in them by ultra high-performance liquid chromatography tandem mass spectrometry (UHPLC-MS). The concentration-time data for each individual were plotted by noncompartmental analysis for the whole three routes. Following intravenous administration, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…High-resolution mass spectrometry has been widely used to aid with drug discovery and development (30)(31)(32)(33). Using this technique, our research team has previously illustrated the pharmacokinetics (22) and metabolic profiles of VLM (24) and TIA (23). In the current study, the comparative metabolism of RTM in animal and human liver microsomes was investigated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…High-resolution mass spectrometry has been widely used to aid with drug discovery and development (30)(31)(32)(33). Using this technique, our research team has previously illustrated the pharmacokinetics (22) and metabolic profiles of VLM (24) and TIA (23). In the current study, the comparative metabolism of RTM in animal and human liver microsomes was investigated.…”
Section: Discussionmentioning
confidence: 98%
“…According to the European Medicines Agency (EMA), pleuromutilin incubated with hepatic cytochrome P450 (CYP) enzymes is prone to be extensively hydroxylated at the 1␤, 2␤, and 8␣ positions (21). Recently, our research team has conducted many studies on the pharmacokinetics (22) and in vitro and in vivo metabolism of VLM and TIA (23,24). However, until now, metabolic information about RTM has remained scarce.…”
mentioning
confidence: 99%
“…Consequently, we performed pharmacokinetic studies in pigs using Form I. Various pharmacokinetic and bioavailability data for valnemulin hydrochloride have been published regarding its use in broiler chickens, rats, Muscovy ducks, layer chickens, ducks, and pigs [2223243031]. However, few studies have reported similar data for valnemulin hydrogen tartrate.…”
Section: Discussionmentioning
confidence: 99%
“…Solubility determination was performed according to the method described by Da et al [322] with some modifications. An excess amount of valnemulin hydrogen tartrate polymorphs were added to 10 mL of ultrapure water at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…The bioavailability of valnemulin is reported to be 74.4% in fasted broiler chickens (Wang et al., 2011 ). A short communication reported a bioavailability of 52.6% in broilers with no information on the fed or fasted status (Sun et al., 2017 ). In pigs, a study suggested a bioavailability of 59% but the confidence on this value is low due to the fact that the animals receiving treatment by oral and intravenous routes were not comparable (Yuan et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%